If α , β , γ are the roots of the equation x 3 − 6 x 2 + 1 0 x + 1 = 0 then α 2 + β 2 1 + β 2 + γ 2 1 + α 2 + γ 2 1 = B A where A and B are co-prime. Find B − A
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
There is no problem with your way. +1 for it! This problem is inspired from this one, and I solved it in a similar fashion.
Write the required sum as S = 1 6 − α 2 1 + 1 6 − β 2 1 + 1 6 − γ 2 1 and then use partial fraction decomposition. Lastly, use the fact that for a polynomial f ( x ) with roots r i , f ( x ) f ′ ( x ) = i = 1 ∑ n x − r i 1 After the partial fraction step, you could also use a root transform. But anyway, my method is as long as yours.. :)
Log in to reply
It may be as long, but it is a much more elegant method! :) Thx for posting it :)
i did same
lets review vieta's ⎩ ⎪ ⎨ ⎪ ⎧ α + β + γ = 6 α β + α γ + β γ = 1 0 α β γ = − 1 and lets compute some important terms α 2 + β 2 + γ 2 = ( α + β + γ ) 2 − 2 ( α β + β γ + γ α ) = 6 2 − 2 0 = 1 6 α 2 β 2 + α 2 γ 2 + β 2 γ 2 = ( α β + β γ + γ α ) 2 − 2 α β γ ( α + β + γ ) = 1 0 2 + 1 2 = 1 1 2 now, the Numerator = = = = = ( β 2 + γ 2 ) ( α 2 + γ 2 ) + ( α 2 + β 2 ) ( α 2 + γ 2 ) + ( α 2 + β 2 ) ( β 2 + γ 2 ) α 4 + β 4 + γ 4 + 3 ( α 2 β 2 + α 2 γ 2 + β 2 γ 2 ) ( α 2 + β 2 + γ 2 ) 2 + ( α 2 β 2 + α 2 γ 2 + β 2 γ 2 ) 1 6 2 + 1 1 2 3 6 8 the denominator ( α 2 + β 2 ) ( β 2 + γ 2 ) ( γ 2 + α 2 ) by Daniel Liu 's identity ( a + b ) ( b + c ) ( c + a ) = ( a + b + c ) ( a b + b c + c a ) − a b c so, = ( α 2 + β 2 ) ( β 2 + γ 2 ) ( γ 2 + α 2 ) = ( α 2 + β 2 + γ 2 ) ( α 2 β 2 + α 2 γ 2 + β 2 γ 2 ) − α 2 β 2 γ 2 = 1 6 × 1 1 2 − 1 = 1 7 9 2 − 1 = 1 7 9 1 so the whole expression is 1 7 9 1 3 6 8 and 1 7 9 1 − 3 6 8 = 1 4 2 3
For easy typing, let α = a , β = b , γ = c
From Vieta's formula, we know that:
a + b + c = 6 a b + a c + b c = 1 0 a b c = − 1
To make the sum a bit simpler to calculate, find a 2 + b 2 + c 2 using Newton's sums:
a 2 + b 2 + c 2 = ( a + b + c ) 2 − 2 ( a b + a c + b c ) = ( 6 ) 2 − 2 ( 1 0 ) = 1 6
Our required sum is:
a 2 + b 2 1 + b 2 + c 2 1 + a 2 + c 2 1 = 1 6 − c 2 1 + 1 6 − a 2 1 + 1 6 − b 2 1 = ( 1 6 − a 2 ) ( 1 6 − b 2 ) ( 1 6 − c 2 ) ( 1 6 − a 2 ) ( 1 6 − b 2 ) + ( 1 6 − b 2 ) ( 1 6 − c 2 ) + ( 1 6 − a 2 ) ( 1 6 − c 2 ) = 1 6 3 − 1 6 2 ( a 2 + b 2 + c 2 ) + 1 6 ( a 2 b 2 + a 2 c 2 + b 2 c 2 ) − a 2 b 2 c 2 3 ( 1 6 2 ) − 2 ( 1 6 ) ( a 2 + b 2 + c 2 ) + a 2 b 2 + a 2 c 2 + b 2 c 2 = 1 6 3 − 1 6 2 ( 1 6 ) + 1 6 ( a 2 b 2 + a 2 c 2 + b 2 c 2 ) − ( a b c ) 2 3 ( 1 6 2 ) − 2 ( 1 6 ) ( 1 6 ) + a 2 b 2 + a 2 c 2 + b 2 c 2 = 1 6 3 − 1 6 3 + 1 6 ( a 2 b 2 + a 2 c 2 + b 2 c 2 ) − ( − 1 ) 2 3 ( 1 6 2 ) − 2 ( 1 6 2 ) + a 2 b 2 + a 2 c 2 + b 2 c 2 = 1 6 ( a 2 b 2 + a 2 c 2 + b 2 c 2 ) − 1 1 6 2 + a 2 b 2 + a 2 c 2 + b 2 c 2
Now, all we need to do is find this:
( a b + a c + b c ) 2 = a 2 b 2 + a 2 c 2 + b 2 c 2 + 2 ( a 2 b c + a b 2 c + a b c 2 ) a 2 b 2 + a 2 c 2 + b 2 c 2 = ( a b + a c + b c ) 2 − 2 a b c ( a + b + c ) = ( 1 0 ) 2 − 2 ( − 1 ) ( 6 ) = 1 1 2
Substitute this value in:
1 6 ( a 2 b 2 + a 2 c 2 + b 2 c 2 ) − 1 1 6 2 + a 2 b 2 + a 2 c 2 + b 2 c 2 = 1 6 ( 1 1 2 ) − 1 1 6 2 + 1 1 2 = 1 7 9 2 − 1 2 5 6 + 1 1 2 = 1 7 9 1 3 6 8
⟹ A = 3 6 8 , B = 1 7 9 1 , B − A = 1 7 9 1 − 3 6 8 = 1 4 2 3
Problem Loading...
Note Loading...
Set Loading...
Not sure whether there's a better solution without bashing like I'll be: First, notice that by Vieta's Formula , we get the following relations between the 3 roots: ⎩ ⎪ ⎨ ⎪ ⎧ α + β + γ = 6 α β + α γ + β γ = 1 0 α β γ = − 1 Here I'll be manipulating the above 3 equations (labelled [1], [2], [3] in order of up to down) to give the following expressions to solve the following numerator and denominator expressions. (It is more intuitive to come up with the expressions for denominator and numerator first but I chose to present it this way so that solution will be cleaner.) { α 2 + β 2 + γ 2 = [ 1 ] 2 − 2 [ 2 ] = 1 6 α 2 β 2 + α 2 γ 2 + β 2 γ 2 = [ 2 ] 2 − 2 [ 3 ] [ 1 ] = 1 1 2 Simply converting the RHS expression into 1 fraction (with a common denominator) we get:
Numerator = = = = = ( β 2 + γ 2 ) ( α 2 + γ 2 ) + ( α 2 + β 2 ) ( α 2 + γ 2 ) + ( α 2 + β 2 ) ( β 2 + γ 2 ) α 4 + β 4 + γ 4 + 3 ( α 2 β 2 + α 2 γ 2 + β 2 γ 2 ) ( α 2 + β 2 + γ 2 ) 2 + ( α 2 β 2 + α 2 γ 2 + β 2 γ 2 ) 1 6 2 + 1 1 2 3 6 8
Denominator = = = = ( α 2 + β 2 ) ( α 2 + γ 2 ) ( β 2 + γ 2 ) ( 1 6 − α 2 ) ( 1 6 − β 2 ) ( 1 6 − γ 2 ) 1 6 3 − ( α β γ ) 2 − 1 6 2 ( α 2 + β 2 + γ 2 ) + 1 6 ( α 2 β 2 + α 2 γ 2 + β 2 γ 2 ) 1 7 9 1
Therefore, B − A = 1 7 9 1 − 3 6 8 = 1 4 2 3 . . We're done. :)
Intuition Basically when faced with such question - finding a value of an expression in terms of some roots, the most straightforward method is to use Vieta's to derive the first few relations between the roots. Then, we manipulate the equations (from Vieta's) as well as the given expression to get the value we desire.